Information Provision to The Disadvantaged: A Proposal For Extension Of Library And Information Services To Refugees In Oru Camp, Ogun State, Nigeria. (Global Journal of Human-Social Science, 2012)
Information is a public good which must not be denied anyone regardless of socioeconomic status or political affiliation However some groups of individuals such as political refugees are underserved with this essential commodity This paper presents an assessment of information need and information provision to refugees in Oru camp Ogun state Nigeria The paper includes a review of some library and information services to refugees in Myanmar and Zambia and concludes with proposal for library and information services to the refugees
Keywords: Refugees; Information; Information provision; Library and information services; Disadvantaged; Oru; Nigeria